TEKANAN PENDUDUK TERHADAP LAHAN PERTANIAN SAWAH PER KELURAHAN DI KOTA SOLOK - badri ahmad; Ratna Wilis (JURUSAN GEOGRAFI FIS UNP, 2020)
This study was conducted in the Solok city with the aim to determine variations in population pressure on rice fields in the city of Solok. The source of research data is secondary data. The method of calculating population pressure (TP) in research uses the Otto Soemarwoto model II formula. The research is described by quantitative analysis presented in tables and maps. The results showed in general the city of Solok had occured population pressure (TP> 1). The urban village with low category are Nan Balimo (3.93) and Laing (4.45). The urban Village with medium category are VI Suku (9.88), Sinapa Piliang (9.68), IX Korong (8.23), Aro IV Korong (11.65), Koto Panjang (11.76), Tanjung Paku (8.98), and Kampung Jawa (10.26). The urban village with high categories are Tanah Garam (18.14), Pasar Pandan Air Mati (16.46), Kampai Tabu Karambia (17.04), and Simpang Rumbio (16.84). The rate of population growth that continues to increase and land use change will lead to population pressure on agricultural land.